Monopoly Analysis of a Limited Liability of State-Owned Enterprises (SOEs) - Machmud, Aris; Mubarok, Djihadul; Majid, Abdul; Aprilianda, Nurini (Jurnal Penegakan Hukum dan Keadilan, 2022)
Monopoly is regulated in the regulation of State-Owned Enterprises (SOEs) as the right to regulate (bestuur) all state resources as mandated by the constitution of Article 33 of the 1945 Constitution and also the BUMN Law Number 19 of 2003 where one of them is a company that is an entity a government-owned business in the form of a limited liability company. The capital is divided into wholly or at least 51 percent of the shares owned by the Republic of Indonesia with the main objective of pursuing profit. In the case of SOEs, corporate actions are determined by the direction of state policies in their economy. Problem formulation based on the above background, is monopolistic and de-monopoly practices against SOEs, inconsistency of the government? This research used normative juridical with a quantitative analytical approach and examines literature studies that conclude. The study results showed that corporate action was not doubt or inconsistency in implementing a state monopoly. However, this holding was to increase the capacity and existence of SOEs as agents of development and the state in managing resources related to many people’s lives.